PERSONAL VALUES PROFILING AND ADVANCE CARE PLANNING. Issue 2 (1st June 2013) - Corke, Charlie
Abstract : Many people find it difficult to think about dying and to refuse medical treatments. This makes Advance Care Planning a challenge. In contrast, thinking about values is much easier. Exploring values can reveal how consistent views are and can also provide a profile of values that can give insight to how the individual thinks about issues relating to death, debility, medical treatment and dependency. People have reacted positively to completing the Personal Values Profile. No negative feedback has been received. Several users have commented that the survey was confronting but important. Many stated that they planned to share the Personal Values Profile report with their family and doctors. This is very encouraging as this may Personal Values Profiling has been tested in a Best-Worst Scoring System involving over 1000 people aged 55 and over. This reveals that only a small minority of people have values that support the medical default position (ie, to do whatever possible to save life, whatever the burden of treatment and however poor the outcome may be). The Personal Values Profile results have been analysed for clustering of values within the individual responses. This reveals 3 distinct groups: Group 1 (7%) believe in extending life no matter what the consequences Group 2 (32%) view quality of life as important but are willing to accept some limitations Group 3 (61%) view quality of life as paramount and would rather die than accept limitations Sub-analysis of responses by patients aged over 80 reveals that Group 3 are even more highly represented in this group. Group 1 remains at 7% so the increase is due to older individuals ceasing to accept limitations so moving from Group 2 to Group 3. The finding that the majority opinion (Group 3) takes the view that there are situations that are worse than death is of great import and suggests that the medical default (to save life at any cost) fails a large proportion of patients. This finding also suggests that Advance Care Planning is required for a large proportion of the population. The utility of Personal Values Profile report to directly assist medical decision making, or to facilitate formal Advance Care Planning, remains to be demonstrated.